NEW STUDENTS' PERCEPTIONS OF THE IMPLEMENTATION OF THE INDONESIAN LANGUAGE MATRICULATION PROGRAM AT THE BEGINNING OF THE ACADEMIC YEAR - Ernie Bertha Nababan; Syihabuddin Syihabuddin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
The matriculation program serves as a crucial step in assisting new students in understanding and adapting to the academic environment of higher education, particularly for those coming from diverse educational backgrounds. This study aims to explore the perceptions of new students participating in the Indonesian language matriculation program concerning the implementation of the program and its impact on their preparedness for attending classes. A survey was conducted with 39 students using a questionnaire that included various aspects such as the atmosphere, instructor guidance, course materials, and teaching methodologies. The survey results indicate that the majority of respondents hold a positive view towards the matriculation program. Specifically, 39% of students agreed or strongly agreed that the matriculation atmosphere was enjoyable. Furthermore, 74% of students felt that the guidance provided by lecturers and tutors was effective, 62% agreed that the materials taught were useful, and 69% stated that the content was relevant to their academic needs. The majority also concurred that the matriculation program aided them in preparing for their studies. The conclusions drawn from this research suggest that the matriculation program successfully provided the support necessary for new students to prepare for their academic journey. However, there is a need for increased variation in teaching methods and the relevance of materials to adequately meet the needs of all students. Recommendations for program administrators include the regular evaluation and updating of curriculum content and teaching methods in the matriculation program to better accommodate the diversity of participants' educational backgrounds